2021
DOI: 10.3390/nu13093081
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a School-Based Gardening, Cooking, Nutrition Intervention on Diet Intake and Quality: The TX Sprouts Randomized Controlled Trial

Abstract: School gardens have become common school-based health promotion strategies to enhance dietary behaviors in the United States. The goal of this study was to examine the effects of TX Sprouts, a one-year school-based gardening, cooking, and nutrition cluster randomized controlled trial, on students’ dietary intake and quality. Eight schools were randomly assigned to the TX Sprouts intervention and eight schools to control (i.e., delayed intervention) over three years (2016–2019). The intervention arm received: f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 88 publications
1
34
0
3
Order By: Relevance
“…The primary objective of the TX Sprouts intervention was to improve dietary intake (i.e., fruit and vegetable consumption) and cardiometabolic health [ 28 ]. The intervention increased vegetable intake [ 26 , 27 ], but the present study showed no impact on breakfast consumption. While it was not a primary focus of the intervention curriculum, one of the eighteen lessons in the intervention encouraged breakfast consumption and taught (1) the healthy components of a breakfast meal, (2) the health benefits of breakfast consumption, and (3) choosing healthy breakfast options from the school cafeteria.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The primary objective of the TX Sprouts intervention was to improve dietary intake (i.e., fruit and vegetable consumption) and cardiometabolic health [ 28 ]. The intervention increased vegetable intake [ 26 , 27 ], but the present study showed no impact on breakfast consumption. While it was not a primary focus of the intervention curriculum, one of the eighteen lessons in the intervention encouraged breakfast consumption and taught (1) the healthy components of a breakfast meal, (2) the health benefits of breakfast consumption, and (3) choosing healthy breakfast options from the school cafeteria.…”
Section: Discussionmentioning
confidence: 64%
“…This secondary analysis from an experimental study used baseline and post-intervention data from TX Sprouts, a school-based cluster randomized controlled gardening, cooking, and nutrition intervention that was originally designed to increase fruit and vegetable intake and decrease sugar-sweetened beverage intake, obesity parameters, and blood pressure [ 26 , 27 ]. The complete methods of the TX Sprouts intervention have been described previously [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…A review of the impact of school gardens on student performance revealed consistent positive outcomes. Studies showed that maintaining a school garden resulted in positive health impacts like nutritional benefits (Landry et al, 2021) and well-being impacts derived from satisfaction and pride from nurturing the plants (Ohly et al, 2016). However, a divide exists between those teachers who are willing to use the school garden in their lessons and those who are not.…”
Section: Discussionmentioning
confidence: 99%
“…While prior research suggests that gardening may affect school-age children’s learning ( Berezowitz et al, 2015 ; Wells et al, 2015 ) and diet ( Davis et al, 2015 ; Skelton et al, 2019 ), few studies have focused on the influence of garden interventions on preschool-age children, when effects may be particularly potent. Moreover, many prior studies face methodological limitations such as short duration, small sample sizes, absence of a control group, or lack of random assignment, which compromise causal conclusions (i.e., internal validity; Ohly et al, 2016 ; Savoie-Roskos et al, 2017 ; Landry et al, 2021 ). The goal of this randomized controlled trial (RCT) is to increase understanding of the impact of hands-on gardening on preschool children’s FV knowledge, FV liking, and consumption of FV during snack sessions.…”
Section: Introductionmentioning
confidence: 99%